HAMBATAN UMKM DALAM MENINGKATKAN PENJUALAN DI ERA DIGITALISASI PADA PASAR MODERN LIMBOTO - Muh Noval Adam; Joice Machmud; Sri Hantuti Paramata (Universitas Muhammadiyah Gorontalo, 2026)
This study aims to identify and analyze the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in increasing sales, viewed from the aspects of digital marketing, capital, and business management. The research method used is a qualitative descriptive approach, focusing on an in-depth understanding of the actual conditions experienced by MSME actors. The results of the study indicate that the main constraints include: (1) a lack of understanding and skills in digital marketing and the use of marketplaces; (2) limitations in capital structure, which still largely rely on personal funds; and (3) business management that is not yet well-organized, including task division and human resource management that have not been optimized. These findings serve as a basis for formulating more effective business development strategies.